"They're just, like, there": A constructivist grounded theory study of student experiences with school resource officers. Issue 8 (31st March 2022) - Layton, Danielle; Gerstenblatt, Paula
Abstract: School‐based policing has become common practice, but there is limited qualitative research examining what meanings students make of police presence in their schools. This study sought to understand how students construct narratives of police presence in their schools based on their experiences with school resource officers (SROs). Drawing on constructivist grounded theory methodology with a sample of 17 students, this study found that students are continuously integrating multiple conflicting narratives about SROs: students experience SROs as an established yet ambiguous presence, which produces mixed feelings of reassurance, wariness, and intimidation. Students manage the conflicts between these narratives by positioning school‐based police as a fixed structure with pitfalls and positives but no alternatives. Additionally, students experience SROs as being available to them in relational capacities. The primary recommendations from this study are for schools and communities to (1) reconsider the appropriateness of SRO programs with student perspectives at the center of dialogue, and (2) invest in non‐law enforcement school‐based professionals who students experience as available and relational.